Penguatan Pembelajaran Al-Qur'an melalui Metode Talaqqi di Pondok Pesantren Terpadu Al-Chodidjah - 'Azah, Nur; Sholeh, Muh Ibnu; Tasya, Dinar Ayu; Munawwarah, Munawwarah; Abror, Sirojuddin; Mintarsih, Mimin; Rosyidi, Hasyim (Al Mu'azarah: Jurnal Pengabdian Kepada Masyarakat, 2024)
The Program for Strengthening Al-Qur'an Learning through the Talaqqi Method at Pondok Pesantren Terpadu Al-Chodidjah aims to enhance the quality of Al-Qur'an education by integrating the traditional talaqqi method with modern technology. The program, which includes intensive training for teachers and ustadz, the development of interactive learning media, and small group student mentoring, was conducted from February 15, 2024, to August 30, 2024. It successfully improved the educators' competence in teaching the Al-Qur'an and utilizing technology. The learning media developed, including audio recordings and tajwid modules, significantly increased students' understanding and motivation. Intensive mentoring yielded significant improvements in students' reading skills and comprehension. Challenges such as time constraints were addressed through schedule adjustments and the empowerment of ustadz in material creation. This program demonstrated a positive impact on improving the quality of Al-Qur'an learning and can serve as a model for similar developments in other pesantren.